PENERAPAN METODE TIM DI RUANG RAWAT INAP RUMAH SAKIT ISLAM IBNU SINA YARSI BUKITTINGGI - Sri Hayulita, Sri Hayulita; Chaidir, Reny; Rahmi, Chintya (BPPM Politeknik 'Aisyiyah Sumatera Barat, 2024)
The team method is a method in which a nurse leads a group of other nurses in providing nursing care to a group of patients with the aim of achieving cooperative and collaborative. This study aims to describe the application of the team method in the inpatient room of the Ibnu Sina Yarsi Islamic Hospital in Bukittinggi 2022. This type of research uses a survey study method. The place of research was carried out in the Inpatient Room of the Ibnu Sina Yarsi Islamic Hospital, Bukittinggi. The research sample in the form of nurses in the Inpatient Room amounted to 131 people. The data analysis technique used frequency distribution analysis and descriptive statistics. The average results show that the implementation of the team method: 100% planning has been carried out, 93.9% organizing has been carried out and 6.1% has not been carried out, 98.5% direction has been carried out and 1.5% has not been carried out, 97.7 supervision % has been carried out and 2.3%, 90.8% control has been carried out and 9.2% has not been carried out. An overview of the application of the team method in the Inpatient Room of the Ibnu Sina Yarsi Islamic Hospital in Bukittinggi in 2022 has been carried out well.